Prospective, Multicenter Evaluation of a Polyherbal Supplement alongside Standard-of-Care Treatment for Mild Knee Osteoarthritis - Zbigniew Żęgota; Joanna Goździk; Joanna Głogowska-Szeląg (Advances in Orthopedics)
Background. This study aimed to provide clinical information on general and joint performance from individuals taking Tregocel® (containing curcuminoid and extracts of the herbs Harpagophytum procumbens, Boswellia serrata, Apium graveolens, and Zingiber officinale) alongside a standard therapy of symptomatic mild knee osteoarthritis (OA). Methods. This was a multicenter, open-label, prospective, single-arm study, in which Tregocel® was supplemented for 36 weeks. Participants with symptomatic mild knee OA requiring pharmacologic treatment for pain were enrolled. Physical performance (6-minute walk test, WOMAC-pain and functional domain, and heel-thigh distance flexion test), general performance (WOMAC questionnaire), and VAS (Visual Analogue Scale) assessment of knee pain, as well as anti-inflammatory and analgesic medication consumption, were assessed. Results. Between January and April 2019, 107 participants were enrolled and analysed in per protocol population. Mean age was 59.7 (SD 10.8) years, and there were 68.2% women. Mean observation time was 291.1 (SD 7.7) days. Mean increase in 6MWT result observed at the end of the study was 26.0 (SD 30.4) m (p<0.001). Median VAS score decreased from 60.0 (IQR 50–72) mm at the beginning of the study to 21.0 (IQR 14–30) mm after 36 weeks of product administration (p<0.001). Regular knee OA medications were taken in 99.1% of subjects at baseline decreasing to 55.1% at the end of the Tregocel® supplementation. Conclusions. During Tregocel® supplementation, participants observed improved functional capacity confirmed in the distance in 6MWT and in the heel-thigh distance flexion test, decreased level of pain, and improved WOMAC scores for all domains.